Respuesta :
1) tan^2(x)*csc^2(x)-1/tan^2(x)
= tan^2(x)*csc^2(x)/tan^2(x) - 1/tan^2(x)
= csc^2(x)-cot^2(x)
=(1+cot^2(x))-cot^2(x)
= 1
2) (cos x (sec x +1)/(sec x -1)(sec x +1)) + (cos x (sec x -1)/(sec x -1)(sec x +1))
= (1+ cos x)+ (1 - cos x)/(sec^2x-1)
= 2/ tan^2(x)
3) Find the missing side for triangle A and triangle B, 'a' lies in quadrant II it is positive, b is in quadrant III so it is negative. when you have found your sides plug it into the identity for tan(a-b) which is tan (a) - tan (b)/1+(tan a)(tan b), and simplify to find your answer.
4) I think it is c. not sure though
= tan^2(x)*csc^2(x)/tan^2(x) - 1/tan^2(x)
= csc^2(x)-cot^2(x)
=(1+cot^2(x))-cot^2(x)
= 1
2) (cos x (sec x +1)/(sec x -1)(sec x +1)) + (cos x (sec x -1)/(sec x -1)(sec x +1))
= (1+ cos x)+ (1 - cos x)/(sec^2x-1)
= 2/ tan^2(x)
3) Find the missing side for triangle A and triangle B, 'a' lies in quadrant II it is positive, b is in quadrant III so it is negative. when you have found your sides plug it into the identity for tan(a-b) which is tan (a) - tan (b)/1+(tan a)(tan b), and simplify to find your answer.
4) I think it is c. not sure though
Hello,
Then the answer i 1/(sin²θ)
Let's assume x=θ ( for the typo)
[tex] \dfrac{tan^2x+1}{tan^2x} [/tex]
[tex]=1+\dfrac{cos^2x}{sin^2x} [/tex]
[tex]=\dfrac{sin^2x+cos^2x}{sin^2x} [/tex]
[tex]=\dfrac{1}{sin^2x} [/tex]
Then the answer i 1/(sin²θ)
Let's assume x=θ ( for the typo)
[tex] \dfrac{tan^2x+1}{tan^2x} [/tex]
[tex]=1+\dfrac{cos^2x}{sin^2x} [/tex]
[tex]=\dfrac{sin^2x+cos^2x}{sin^2x} [/tex]
[tex]=\dfrac{1}{sin^2x} [/tex]